Os processos formativos de licenciandos em Física do IFMT : narrativas sobre o ser professor e a ação de ensinar - Mariani, Fábio (2016)
The present thesis is part of the discussions about teacher training with emphasis on the initial training phase. It has as its central theme the training processes of the undergraduates, within the new contexts which outline Degree Courses in the Federal Institutes of Education, Science and Technology (IFs) and is structured from the central question: how do the undergraduates conceive and construct meanings about “being a teacher” in the initial training process in the context of a degree course in the Federal Institute of Mato Grosso (IFMT) and how they perceive and understand these training experiences in their process of teacher identity construction? The main aim of the research lies in understanding how the undergraduates of the IF Physics course from Pontes e Lacerda conceive/understand the idea of becoming teachers throughout their training – to be a teacher – and which constructs/knowledge manifest on the action of teaching in the process of becoming a teacher. The theoretical bases which give support to the research work are structured in discussions about teacher training, emphasizing the initial training, as well as discussions about teachers professional identities, comprised in the continued processes of teachers’ professional development. The theoretical-methodological option which guides the research is based on the presuppositions of the narrative inquiry. For the composition of the field texts, which taken together makes the narrative of each participant, a group of discussions and reflections was set up, in which the undergraduates had the opportunity to tell their stories about their experiences lived in the initial training, which prompted questions, discussions and reflections. The process of interpretation and analysis of field texts was built from the perspective of “composition of the senses”. The results of the research point to reflections on the complex, continuous and multidimensional training process that shows the sense composition about being and becoming a teacher, constituted along the experience of initial training. They also point to the tensions, resistances and conflicts which marked the initial process of construction of professional identities of the undergraduates and, in this movement the experience of Supervised Curriculum Stages gains prominence. They are learnings which mark the sense fields constructed and narrated by the undergraduates from their training experiences: the domain of the specific content, as well as other necessary knowledge for teaching; the need to think didactically the scientific knowledge in such a way that they can be transformed into “teachable” knowledge; the teacher’s role in mediating the learning process; time and class management and the “domain of the classroom”; the relationship between teacher and student marked by the care the teacher should have towards students; the search for experimental classes as a teaching strategy and the demystification of the subject Physics.